Penguatan Akses Keadilan melalui Pelatihan Paralegal Berbasis Komunitas Muhammadiyah di Lampung Utara - Kesuma Dinata, M. Ruhly; Hartono, Hartono (Westscience Press, 2025)
Inequality of access to justice is still a serious challenge in various regions of Indonesia, including North Lampung. Vulnerable groups such as women, children, and Muhammadiyah cadres often face violence and discrimination without adequate legal assistance. Muhammadiyah as a modern Islamic organization committed to the values of social justice needs to take a strategic role in strengthening the capacity of the community through legal aid programs. This research aims to describe Muhammadiyah's strategy in increasing public legal awareness through community-based paralegal training. The implementation method combines a participatory approach, local needs analysis, and the use of an active learning model. The results showed that paralegal training provided increased legal understanding, courage in advocacy, and the formation of a network of legal assistants based on progressive Islamic values. This article concludes that paralegal training is not just a form of devotion, but a transformative strategy for grounding social justice at the grassroots level.